Efectos de la harina de cascara de naranja en la dieta de cuyes (Cavia porcellus), en etapa de crecimiento. - Guerrero Mackliff, Luis (2021)
A documentary (books, magazines, indexed articles) and bibliographic research was carried out. Taken from the database of different published works about the implementation of orange peel in the diet of different animal species, through the inductive deductive method with the aim of generating a sustainable, sustainable and environmentally friendly alternative to the diet. of the guinea pigs (Cavia porcellus) in the growth stage by using orange peel flour, which has excellent nutritional characteristics and, as it is considered a waste product, costs will be reduced for the small producer in rural areas, so that In this way, they have access to the elaboration of a balanced diet since the high costs of raw materials are one of the main reasons why the genetic potential of the guinea pig cannot be exploited due to the fact that it receives a deficiency diet obtaining animals with low weights and longer time for the animals to leave, generating lower economic income, which limits the progress of the families of the rural sector